Airway dysfunction in elite athletes - O`Donovan, J.; Koehle, M.; McKenzie, D. (Triathlon Medicine, 2019)
Training and competing in elite triathlon events challenge the limits of human performance. While it is generally felt that the respiratory system does not limit performance, several conditions exist during heavy physical work that may influence success. Exercise-induced arterial hypoxemia and expiratory flow limitation can occur in healthy athletes and may affect performance. Exercise-induced asthma and bronchoconstriction are common in sports with a major endurance component, as well as exposure to allergens, such as chlorine or air pollution. Diagnosis of respiratory conditions should be made with objective tests of respiratory function and the management of the athlete with asthma should follow current national or international guidelines. Education is an essential component; environmental control and the identification of triggers are also important. Warm up and individual pharmacotherapy are necessary. Athletes must comply with the WADA code for use of all medications.